Ongoing organizational reforms of the People’s Liberation Army Air Force - Allen, Kenneth W. (2021)
Since the Chinese Communist Party’s (CCP) Central Military Commission launched a major reorganization of the entire People’s Liberation Army (PLA) in early 2016, the PLA Air Force (PLAAF) has followed up with its own reforms at all levels. In February 2016, the changes entailed ‘above the neck’ reforms at PLAAF Headquarters and reduced the number of Military Region Air Force Headquarters from 7 to 5, renaming them Theatre Command Air Forces. Changes in 2017 focused on ‘below the neck’ reforms by creating a ‘base-brigade’ structure by reforming several command posts into bases; abolishing fighter, fighter-bomber, and ground attack aircraft air divisions; replacing air regiments with brigades; as well as changing the name of its former 15th Airborne Corps to Airborne Corps. Whilst the PLA leadership has moved ahead with pushing the PLAAF towards becoming a modern air force with enhanced aerial power alongside greater interoperability with the other PLA services, the reconstitution of its organizations has nevertheless led to a fallout due to policy changes concerning its rank-and-file.